(untitled) (Physical Education, Health and Social Sciences, 2025)
Lilies (Liliaceae family) are economically very important bulbous ornamental crop. Cultivars of this crop are used as cut flowers and garden plants, and are now indispensable for horticultural use. Genus Lilium of the family Liliaceae consists of more than 80 species and these species are divided into 7 sections (Comber 1949; Lighty 1968; de Jong 1974). The diversity of flower shape, colour, fragrance and other physiological and phenotypic characteristics are found in its wild species which are dispersed in the Northern Hemisphere (10 to 60 ), mainly in North America and Europe, Asia. Especially, China, Japan, Korea and Nepal are the gene centres of this genus around the whole world. Yunnan province is the famous habitat of the Lilium species in China in particular. This crop has been subjected to extensive interspecific hybridization followed by selection. Additionally, spontaneous polyploidization has played a role in its evolution. In lilies, there is a tendency to replace diploids with polyploid cultivars. The introduction of molecular cytogenetic techniques such as genomic in situ hybridization (GISH) permitted the detailed studies of genome composition in lily. In addition, this review presents the information about the future development regarding breeding in lilies.